A Study of Individual Characteristics and Organization Characteristics Antecedents of Protean Career Attitude and Relationship with Adaptive Performance - Choi, Anna; Tak, JinKook (Korean Journal of Industrial and Organizational Psychology, 2023)
The purpose of this study was to examine the relationships among Protean Career Attitude, Flexibility, Strengths Use, Job Autonomy, Growth Opportunity and Adaptive Performance. Specifically, first, this study investigated the influence of individual Characteristics(Flexibility, Strengths Use) and Organization Characteristics(Job Autonomy, Growth Opportunity) on Protean Career Attitude. Second, this study examined the influence of Protean Career Attitude on Adaptive Performance 2 month later. Third, this study examined the influence of individual Characteristics(Flexibility, Strengths Use) and Organization Characteristics(Job Autonomy, Growth Opportunity) on Adaptive Performance 2 month later and partially meditated by Protean Career Attitude. Data was collected from 1,000 Korean employees who had more than 3 years of working experiences in various organizations for the first survey via online. After 2 months, 500 data was collected from the 1st survey respondents. The findings are as follows: First, there were positive effect of Flexibility, Strengths Use, Job Autonomy on Protean Career Attitude. However, Growth Opportunity had positive effect on Protean Career Attitude only in simple regression. Second, there was positive effect of Protean Career Attitude on Adaptive Performance 2 months later. Third, individual Characteristics(Flexibility, Strengths Use) and Organization Characteristics(Job Autonomy, Growth Opportunity) on Adaptive Performance was partially mediated by Protean Career Attitude. Based on these results, implications and limitations of this study with the directions for future research were discussed.